Transparency of medicines data and safety issues–a European/US study of doctors' opinions: what does the evidence show?. Issue 9 (20th October 2016) - Löfstedt, Ragnar; Way, Dominic; Bouder, Frederic; Evensen, Darrick
Abstract : Over the past 10 years, European pharmaceutical regulators (especially the European Medicines Agency [EMA]) have enacted a wave of transparency policies. Since 2010, the overwhelming majority have focused on releasing more scientific medicines information online and providing open access to regulatory data. Amongst other benefits, EMA expects its policies to build public trust and provide outsiders with a better understanding of regulatory decision-making. Yet, few studies have empirically examined the EMA's transparency policies, especially on the end users of 'transparent' information (e.g. medical doctors or patients). This paper presents standout findings from a November 2014 survey conducted in Spain, Germany, France and the United Kingdom with a sample of 1005 general practitioners and medical specialists treating either multiple sclerosis, rheumatoid arthritis, osteoporosis, idiopathic pulmonary fibrosis or HIV/AIDS. The study found that 76% of respondents think it is a bad idea to release information into the public domain before possible safety issues have been investigated by the regulators and (relevant) pharmaceutical company. The results also suggested that medical doctors in Europe have a poor understanding of pharmaceutical regulatory activities. In particular, the majority were largely unaware of the current activities of the EMA, did not have good knowledge of how the regulators assess the safety of medicines (e.g. only 17% said they had good knowledge of how EMA assess the safety of medicines) and were unfamiliar with regulatory documents frequently used by regulators and industry to discuss the safety of medicines (e.g. in approving a medicine).